2020
DOI: 10.4103/cs.cs_19_71
|View full text |Cite
|
Sign up to set email alerts
|

Auto-rewilding in Post-industrial Cities: The Case of Inland Cormorants in Urban Britain

Abstract: The last forty years have seen a dramatic increase in the number of great cormorants (Phalacrocorax carbo) moving inland away from British coastlines. Britain's largest inland colony currently reside at Walthamstow Wetlands, a nature reserve and functional reservoir system in northeast London, recently branded 'Europe's largest urban wetland'. Here, great cormorants are embroiled in contested ideas of nature. Celebrated by conservationists for their resilience and adaptability, yet hounded by anglers for launc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 64 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Rewilding is "an ambitious and optimistic agenda for conservation, centered on the (re)establishment of ecological processes with a less controlling or coercive management approach by humans" [101] . Most studies about rewilding have focused on what rewilded non-human species, the so-called keystone, flagship, indicator, or umbrella species [103][104][105] , contribute to ecosystem functions and -services [106] . Their ecological engineering capabilities aim to benefit humans, species, or landscapes [107] .…”
Section: Urban Rewildingmentioning
confidence: 99%
See 1 more Smart Citation
“…Rewilding is "an ambitious and optimistic agenda for conservation, centered on the (re)establishment of ecological processes with a less controlling or coercive management approach by humans" [101] . Most studies about rewilding have focused on what rewilded non-human species, the so-called keystone, flagship, indicator, or umbrella species [103][104][105] , contribute to ecosystem functions and -services [106] . Their ecological engineering capabilities aim to benefit humans, species, or landscapes [107] .…”
Section: Urban Rewildingmentioning
confidence: 99%
“…Therefore, urban rewilding is an urban process that is occurring [120,121] as a 'spontaneous, autonomous occupation of [urban] space by nonhuman animals' [122] . Autonomous 'activities of animals themselves' [123] to move and relocate where they previously didn't occur, being 'out of place' or 'invasive' [106] is defined as auto-rewilding. The mobility of various animal, bird, and plant species responding to human activities is more complex and fluid than a simple in/out of place stigma [124] .…”
Section: Urban Rewildingmentioning
confidence: 99%
“…Revitalizing patches of urban land can create possibilities for damaged ecosystems to regenerate, reverting to natural systems and processes that can help address many of the present concerns we face, including climate change, increased flooding risk, poor air quality, pollution and biodiversity loss, and by creating a chain of similar connected areas and networks [31,35,36]. Clancy and Ward (2020) investigated the concept of auto-rewilding in drastically transformed urban and post-industrial contexts [37]. They emphasized that the effects of having auto-rewilded species in post-industrial environments needed to go beyond the negative perception of invasion and harm [37].…”
Section: Introductionmentioning
confidence: 99%
“…Clancy and Ward (2020) investigated the concept of auto-rewilding in drastically transformed urban and post-industrial contexts [37]. They emphasized that the effects of having auto-rewilded species in post-industrial environments needed to go beyond the negative perception of invasion and harm [37]. Recently, Pettorelli et al 2019 identified three main themes in the definitions of rewilding in academic literature, but the meaning can vary depending on the observer's perspective [38].…”
Section: Introductionmentioning
confidence: 99%